2016
DOI: 10.1038/modpathol.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Standardized evaluation of tumor-infiltrating lymphocytes in breast cancer: results of the ring studies of the international immuno-oncology biomarker working group

Abstract: Multiple independent studies have shown that tumor-infiltrating lymphocytes (TIL) are prognostic in breast cancer with potential relevance for response to immune-checkpoint inhibitor therapy. Although many groups are currently evaluating TIL, there is no standardized system for diagnostic applications. This study reports the results of two ring studies investigating TIL conducted by the International Working Group on Immuno-oncology Biomarkers. The study aim was to determine the intraclass correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
181
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(209 citation statements)
references
References 21 publications
12
181
1
5
Order By: Relevance
“…We also propose that, similar to the breast cancer community, a practical and robust scoring system should be developed. 43 Additional issues requiring large-scale study which were not evaluated here include: utility of image analysis; evaluation of stromal CD8 + TILs; consistency across multiple tumor sites per patient; impact of neoadjuvant chemotherapy; 4547 relationships between CD8 + TIL levels, HGSOC molecular subtypes, 4850 common genetic variation, 51 and epidemiologic risk factors; 52 and evaluation of other lymphocyte subsets, such as CD4 + TILs, CD20 + TILs (B cells), tertiary lymphoid structures, and plasma cells. 10,1214,53 Clinically, it will be important to test whether CD8 + TILs predict response to certain therapies including standard chemo- and immune therapy, as, for example, CD8 + TILs predict chemo-response in subtypes of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We also propose that, similar to the breast cancer community, a practical and robust scoring system should be developed. 43 Additional issues requiring large-scale study which were not evaluated here include: utility of image analysis; evaluation of stromal CD8 + TILs; consistency across multiple tumor sites per patient; impact of neoadjuvant chemotherapy; 4547 relationships between CD8 + TIL levels, HGSOC molecular subtypes, 4850 common genetic variation, 51 and epidemiologic risk factors; 52 and evaluation of other lymphocyte subsets, such as CD4 + TILs, CD20 + TILs (B cells), tertiary lymphoid structures, and plasma cells. 10,1214,53 Clinically, it will be important to test whether CD8 + TILs predict response to certain therapies including standard chemo- and immune therapy, as, for example, CD8 + TILs predict chemo-response in subtypes of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Multicenter international ring studies by the international Immuno-oncology Biomarker Working Group demonstrated that reproducible evaluation of TILs using slides is feasible and the software-guided image evaluation is useful [24]. Recommendations by an international TILs working group described that it is still unknown whether RNA or protein classification of TILs shows better performance of prognostic or predictive value than slide morphology and that further evidence of detecting specific subpopulations by IHC is necessary [14].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, presence of tumor infiltrating lymphocytes (TILs) has been shown to correlate with better prognosis of several solid cancers including MM, 7 colon carcinoma, 8 ovarian cancer 9 and breast cancer. 10 This is supported by accumulating data linking response to immune therapy with a brisk infiltration of T cells in the tumor. 7 , 11 , 12 …”
Section: Introductionmentioning
confidence: 88%